Charge transport in a single molecule transistor probed by scanning tunneling microscopy. Issue 3 (5th January 2018) - Bouvron, Samuel; Maurand, Romain; Graf, Alexander; Erler, Philipp; Gragnaniello, Luca; Skripnik, Maxim; Wiedmann, Dirk; Engesser, Clara; Nef, Cornelia; Fu, Wangyang; Schönenberger, Christian; Pauly, Fabian; et al.
Abstract : Using scanning tunneling microscopy and spectroscopy, we investigate the impact of the gate voltage on the electronic levels of CoPc molecules deposited on top of a graphene/SiO2 /Si device. Abstract : We report on the scanning tunneling microscopy/spectroscopy (STM/STS) study of cobalt phthalocyanine (CoPc) molecules deposited onto a back-gated graphene device. We observe a clear gate voltage ( V g ) dependence of the energy position of the features originating from the molecular states. Based on the analysis of the energy shifts of the molecular features upon tuning V g, we are able to determine the nature of the electronic states that lead to a gapped differential conductance. Our measurements show that capacitive couplings of comparable strengths exist between the CoPc molecule and the STM tip as well as between CoPc and graphene, thus facilitating electronic transport involving only unoccupied molecular states for both tunneling bias polarities. These findings provide novel information on the interaction between graphene and organic molecules and are of importance for further studies, which envisage the realization of single molecule transistors with non-metallic electrodes.